2017
DOI: 10.12688/f1000research.13064.1
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fresh gas flow on wash-in, wash-out time and gas consumption for sevoflurane and desflurane, comparing two anaesthesia machines, a test-lung study.

Abstract: Low-flow anaesthesia is considered beneficial for the patient and the environment, and it is cost reducing due to reduced anaesthetic gas consumption. An initial high-flow to saturate the circle system ( ) is wash-in desirable from a clinical point of view. We measured the wash-in and wash-out times (time to saturate and to eliminate the anaesthetic agent, AA), for sevoflurane and desflurane, in a test-lung with fixed 3 MAC vaporizer setting at different fresh gas flow (FGF) and calculated the consumption of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Some conditions, such as the concentration of inhalation anesthetics before discontinuation or the fresh-gas flow rates, which may affect the time to wash out after discontinuation, were not controlled. The anesthetic concentration that remained at the time of sugammadex administration could be significantly different even with the same duration of T2-T1 [8].…”
Section: Discussionmentioning
confidence: 93%
“…Some conditions, such as the concentration of inhalation anesthetics before discontinuation or the fresh-gas flow rates, which may affect the time to wash out after discontinuation, were not controlled. The anesthetic concentration that remained at the time of sugammadex administration could be significantly different even with the same duration of T2-T1 [8].…”
Section: Discussionmentioning
confidence: 93%
“…A rapid increase in end-tidal desflurane concentration by >5% was found to induce a transient increase in the HR and blood pressure by inducing sympathetic nerve stimulation [ 24 ]. This effect may be noticeable in case of a high fresh gas flow rate and hyperventilation during anesthesia induction [ 25 , 26 ]. However, in most cases, since sevoflurane was switched with <1 MAC desflurane without high fresh gas flow and hyperventilation, it could be maintained stably without significant changes in the HR and MAP.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the F A S reached 1 MAC (2.1%) at 547 ± 83 and 38 ± 6 sec, respectively [5]. Leijonhufvud [12]. Finally, Shin et al performed a wash-in study using a Primus anesthetic machine connected to a test-lung, using a FGF of 0.5, 1, and 3 L•min -1 and setting the F V S to 6%.…”
Section: Jakobsson Et Al Reported a Wash-in In A Test-lung Model Witmentioning
confidence: 99%